Ethnic Tuvans in Tsagaan-Nuur sumon, Mongolia: Research issues - Suvandii, Nadezhda D.; Kuular, Elena M. (The New Research of Tuva, 2017)
The article provides a historical and ethnographic overview of a sub-ethnic group of Tuvans living in sumon Tsagaan Nuur, Khövsgöl aimag, Mongolia. They are known locally as Tsaatans and by self-appellation of Tukha or Tukhalar. Our study is based to the body of existing research and on the field data collected by the authors during expeditions to the Tsaatan area in 2010-11 and 2015-16. A comparative analysis and a summary of existing information call for further research into a number of specific issues.While ethnographic and philological studies of the Tsaatans had begun in mid-20th century, the new stage, spearheaded by scholars from Mongolia and Russia (Tuva), began in the 2000s. ‘Tsaatan’ (i.e. deer owner) is a term applied to the Tukhalars in Mongolia to mark their deer herding-based households. Other issues under discussion include specific details of the Tsaatans’ ethnic history, population size, etc.Mongol acts as the official and interethnic communication language in the sumon. The native Tuvan language is used by the elderly and middle-aged Tukhalars in everyday speech. Youngsters study in Mongol schools where Tuvan language is not an official discipline, which both makes the prospects of language survival dire and threatens the very foundation of the Tsaatans’ ethnic self-identification.Herding the taiga deer still remains the most important economic practice of Tsaatan Tuvans. According to their residence area, Tsaatans are subdivided into deer herders of the taiga of the West and South. Alongside with deer herding, hunting is one of Tsaatan’s main pursuits, which brings them food, clothing and habitation. Domestic utensils are suited for nomadic life, and the staples of Tsaatans’ diet are venison and doe milk. Thus traditional Tsaatan lifestyles are very close to that of deer herders of Tuvans in Tojin rayon, Republic of Tuva.Tsaatans still largely follow their long-time economic practices, which allows them to keep many of their traditions quite recognizable. However, living in close proximity to the Mongols under the domination of Mongol language and culture, as well as the generic process of modernization of local cultures, cannot but affect their self-identification and the language command by the younger generations.The photographs published in the article were taken by the authors during the expedition to sumon Tsagaan-Nuur, Khövsgöl aimag, Mongolia  in September 2011.
Keywords: Tuvans in Mongolia; Mongoliaя; Tsaatans; sub-ethnic group; Tukhalars; deer herders; Tuvan language